Open innovation between university-industry: A review of research trends and practices - Adin Gustina; Nuraini Desty Nurmasari; Jane Su Chuan Liu (Journal of Open Innovation: Technology, Market and Complexity)
This study aims to review papers on open innovation in the university by examining the research profile, open innovation form and the process underpinning, key variables used, and suggestions for potential future studies. This study conducted an analysis of 71 relevant articles among 2.759 obtained from Web of Science and Scopus databases. Content analysis was used to identify significant research concerns and gaps that could be addressed in future studies. This study offers the intersection of open innovation-focused university domains. This paper proposes a conceptual open innovation model in university settings by mapping key characteristics and identifying relevant areas for future research.